INFLUENCE OF BIOLOGIC AND SOCIAL FACTORS ON WORKING CAPABILITY OF WORKERS OF BRAINWORK - S. A. Maksimov; O. A. Ivanova; E. V. Maksimova (Acta Biomedica Scientifica, 2012)
Questionnaire of 285 teachers of comprehensive schools estimated subjective fatigue and possibilities of restoration of working capacity depending on a number of biological and. social factors. From among studied factors the greatest contribution to efficiency of workers of brainwork is brought by indicators of a state of health, in particular chronic incidence, frequency of diseases in a year and. value judgment of health. The age of the worker and. level of satisfaction of the general and. professional requirements have a certain value.